Sensory Processing Sensitivity In Adults With And Without Tension-Type Headache: Moderating Role Of Pain Catastrophizing - Zahra, Yasmeen; Iqbal, Nazia (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Little is known about the relationship between sensory processing sensitivity and tension-type headache. The aim of the present study was to examine the moderating role of pain catastrophizing in the relationship between sensory processing sensitivity and tension-type headache. The sample was selected from Islamabad and consisted of 324 adults (46 men, 278 women). 212 adults were diagnosed with tension-type headache) via a structured questionnaire using the ICHD-3 criteria, and 112 did not report such a health condition. The Highly Sensitive Person Scale was used to measure sensory processing sensitivity, and the Pain Catastrophizing scale was used to measure pain catastrophizing. The results show that tension-type headache was positively correlated with sensory processing sensitivity (r = 0.35, p < 0.01), and this relationship was moderated by pain catastrophizing. This study sheds light on subtle factors contributing to headache disorders. It also informs clinical approaches, emphasizing the role of pain catastrophizing in the sensitivity-headache link, potentially guiding personalized interventions for improved headache management in individuals.